Retinal Haemorrhage in Newborns in Tertiary Care Hospital - Makaju Shrestha, R.; Shrestha, S.; Sharma, S.; Joshi, A.; Shrestha, P.; Shrestha, J. K. (Kathmandu University Medical Journal, 2022)
Background Retinal haemorrhage in new-born is a clinically common neonatal fundus condition. Although, it usually does not affect the development of visual function, entities like macular haemorrhages may lead to amblyopia causing deterioration of visual function. Such scenario leads to downgrade in quality of life of the affected child. Objective To explore the underlying clinical factors associated with retinal haemorrhage in term new-borns. Method A cross sectional study was conducted involving 136 term neonates admitted in the neonatal intensive care unit of Dhulikhel Hospital. Fundus examination was performed within 2 weeks of delivery. Retinal haemorrhage was graded according to their location in three retinal zones. Result Out of 136 cases examined, 44 (32.35%) of the cases had one of the eyes with retinal haemorrhage. Where grade 1 retinal haemorrhage was accounted in majority of the cases. Birth weight, gestational age, mode of delivery, poor Appearance, Pulse, Grimace, Activity, and Respiration (APGAR) Score in 1 and 5 minutes, birth asphyxia, neonatal sepsis and heavy work in antenatal period had statistically significant correlation with occurrence of retinal haemorrhage. Conclusion Our results suggest that spontaneous vaginal delivery, larger birth weight, higher gestational age, birth asphyxia, low Appearance, Pulse, Grimace, Activity, and Respiration score, are risk factors for occurrence of neonatal retinal haemorrhage. It is recommended that in neonates with above high-risk factors should undergo targeted fundus screening for early identification and needful interventions.